2008
DOI: 10.1097/mlg.0b013e3181753354
|View full text |Cite
|
Sign up to set email alerts
|

To POP or Not: Ossiculoplasty in Congenital Aural Atresia Surgery

Abstract: Patients reconstructed with their own intact native chain during aural atresia surgery have better audiometric outcomes than those undergoing OP and are less likely to undergo revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 6 publications
2
18
2
1
Order By: Relevance
“…2 However, hearing results in the current study are comparable with those of other reports, with the postoperative pure tone average in the mild hearing loss range and speech reception thresholds in the borderline normal range. 2,[4][5][6][7][8] In addition, the PORP reconstruction in which the prosthesis is placed on the mobile stapes crural arch appears to be more stable and reliable than the PORP reconstruction in which the prosthesis is placed through the obturator foramen down onto the stapes footplate. 5 Other studies have reported comparable results between intact native ossicular chain reconstruction and ossicular replacement prostheses.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…2 However, hearing results in the current study are comparable with those of other reports, with the postoperative pure tone average in the mild hearing loss range and speech reception thresholds in the borderline normal range. 2,[4][5][6][7][8] In addition, the PORP reconstruction in which the prosthesis is placed on the mobile stapes crural arch appears to be more stable and reliable than the PORP reconstruction in which the prosthesis is placed through the obturator foramen down onto the stapes footplate. 5 Other studies have reported comparable results between intact native ossicular chain reconstruction and ossicular replacement prostheses.…”
Section: Discussionsupporting
confidence: 80%
“…6 The method of reconstruction is dictated by the anatomy at surgery, but if the stapes suprastructure is intact and mobile, the author has found superior results from placing the prosthesis on the suprastructure. 2 One limitation of this study is the lack of long-term data (mean follow-up hearing data are 28 months after surgery; range, 1-58 months). Patients come to the University of Virginia for surgery from around the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial nerve injury is a known complication of aural atresia repair. It has been reported to occur in 0-7% of cases [14][15][16][17][18][19][20][21]. In one study of 99 patients a 6% incidence of transient postoperative facial palsy was noted with a mean total recovery time of 16 weeks [14].…”
Section: Discussionmentioning
confidence: 96%
“…The appropriate ossiculoplasty or stapes surgery may then be performed. Dobratz et al [15], and Lambert [17] compared hearing outcomes for aural atresiaplasty using the native ossicular chain versus ossiculoplasty. Better hearing outcomes and a lower rate of revision surgery were found when the native ossicular chain was preserved versus when ossiculoplasty was performed.…”
Section: Discussionmentioning
confidence: 99%